Activity of Meropenem and Ciprofloxacin in vitro Against Oxacillin Resistant Staphylococcus aureus - Suhad Faisal Hatem Al-Mugdadi (College of Pharmacy / Mustansiriyah University, 2010)
A total of 150 clinical specimens were collected from patients attending Medical city Hospital in Baghdad to isolation and identification Staphylococcus aureus on species level by Api staph 20 system (Biomereux , france). 33 (22%) isolates were isolated from Staphylococcus aureus, this isolates divided according to source of isolate: 15 (37.5%) isolate from wounds, 10 (20%) isolate from bone infection, 7 (50%) isolate from nasal and throat swabs, one (2%) isolate from urine. Thirteen antibiotics were used for sensitivity test; all isolate were resistance to Pencillin (100%), Ampicillin (100%), and while Erythromycin (75.8%). Among the various antimicrobial Oxacillin showed high resisance (69.6%), most effective antibiotics on S. aureus were Vancomycin (100%), Meropenem (100%), while Amikacin and Ciprofloxacin in Percentage 79%, 76% recpectively. In vitro minimum inhibitory concentration (MIC) of Meropenem and Ciprofloxacin were done to determined inhibition effect against all isolates of S. aureus Which is resist to Oxacillin( 23 isolate ) in Serial concentration (4-1024) μg / ml, S. aureus was resistant to Meropenem in percentage 70% in break point ≥ 16, while Ciprofloxacim was resistant in percentage 74% in berak point ≥4.